Clinical tools for evaluating congenital adrenal hyperplasia in resource-limited hospitals: a study at a tertiary hospital in Saudi Arabia - Alhazmi, Daniah; Alabdulqader, Azzam; Almeqbel, Shahad; Alhuthil, Raghad; Alsagheir, Afaf (Frontiers in Endocrinology, 2026)
BackgroundCongenital adrenal hyperplasia (CAH) treatment is complicated by hormonal imbalances, necessitating a dual therapeutic approach to both correct cortisol deficiency and manage androgen overproduction. Unfortunately, hospitals with limited resources lack some necessary standard laboratory tests to manage patients with CAH.ObjectiveTo investigate the interrelation between different monitoring strategies in clinical practice for managing patients with CAH.MethodsThis prospective cross-sectional study involved children with CAH caused by 21-hydroxylase deficiency (21-OHD) treated at King Faisal Specialist Hospital and Research Centre. KFSHRC is not resource-limited; the proposed recommendations are intended for settings that lack full biochemical panels. Univariable, bivariable, and multivariable logistic regression were done for association testing.ResultsThe cohort included 96 children with 21-OHD, predominantly female (61.5%), with a median age of 6 years. Adrenal crises occurred in 20.8% of patients. Most participants were treated with hydrocortisone (97.9%) and fludrocortisone (88.5%), with high reported treatment compliance (90.6%). Biochemical abnormalities were observed in 26% for ACTH, 21.9% for 17-OHP, and 17.7% for testosterone. Biochemical control was significantly associated with treatment compliance (OR 7.6, p = 0.03). In adjusted analyses, androstenedione, ACTH, and testosterone control were strongly associated with 17-OHP control (all p < 0.01). Regarding skeletal outcomes, older age was inversely associated with bone age control, whereas clinical control (OR 11.1, p < 0.01) and controlled androstenedione levels (OR 3.0, p = 0.04) were independent predictors of optimal bone age.ConclusionBased on these findings, we recommend integrating growth velocity monitoring and androstenedione testing into routine visits as valuable indicators for assessing clinical control in 21-OHD children. Yet, larger studies are needed to validate simplified monitoring frameworks for resource-limited hospitals.